(untitled) (Sebha University Conference Proceedings, 2024)
The study aimed to measure the impact of agricultural investment on Libya’s agricultural domestic product during the period (1995-2015), where the importance of research is highlighted by its standard aspect, which seeks to determine the role of agricultural investment in supporting agricultural economic development. The study relied on a model to demonstrate the hypothesis that agricultural investment is a factor helping to achieve growth in agricultural domestic product, and a standard model was used using a programme (Eviews) to test the standard model, the results of the descriptive and metrological analysis have shown that the independent variable (Agricultural investment) has a positive impact on agricultural domestic product in short and long time, and the estimated statistical model is statistically moral ". The study recommended the need to activate the role of information and the use of modern technologies to promote the agricultural sector, and to facilitate the granting of agricultural loans and subsidies through the agricultural bank according to its various areas through the Libyan Agricultural Bank.